Improving Students’ Performance by Using Science Process Skills in The High School’s Physics Curriculum Grade X in Indonesia - Nasri Diana; Ibnu Khaldun; Syahrun Nur (Jurnal Penelitian & Pengembangan Pendidikan Fisika, 2019)
Teaching physic in high schools is very challenging, especially where the teachers understanding of the concept and teaching methods is still limited. It needs an effort to make the teaching more exciting experience for students. This study, therefore, aims to investigate the application of Science Process Skills (SPS) as the scientific skills that can be used to develop and increase science process skills and understanding of physics subject through laboratory activity. This study utilizes experimental design by involving students grade X from Senior High School (SMA) 1 Banda Aceh academic year 2018/2019 as a sample. It follows the competency standard of 2013 Indonesian Curriculum. This study found that there is a positive correlation between the content of the physics syllabus and the science process skills. This condition has contributed positively to the learning achievements of students. The result of pre-and post-test shows the result of post-test has improved after applying this approach. Hence it is recommended that science Process Skills can be promoted as a tool to improve the ability of students in understanding the science concept within the physic, as well as other science subjects.